The Myopectineal Orifice: A Study of Thai Cadavers - Tansawet, Amarit; Rodsakan, Thanakorn; Kasetsermwiriya, Wisit; Lerdsirisopon, Sopon; Techapongsatorn, Suphakarn (Frontiers in Surgery, 2022)
Objective: To determine the myopectineal orifice (MPO) size measured in Thai human cadavers Materials and Methods: A total of 30 human cadavers, comprising 55 groins, were assessed. MPOs were measured in two dimensions: height from the lower border of the conjoin tendon to the upper border of the pectineal ligament and width from the lateral border of pubic tubercle to the medial border of the iliopsoas muscle. Results: The mean MPO size is 7.13 + 0.14 cm in width and 6.66 + 0.32 m in height. The mean width and height in male cadavers are 7.16 + 0.14 and 6.84 + 0.27 cm, respectively. The mean width and height in female cadavers are 7.09 + 0.12 and 6.45 + 0.24 cm, respectively. The mean MPO area is 37.26  0.027 cm2, compared with the area of mesh graft 10*15 cm, 150 cm2. Although the shrinkage of cadaveric tissue and mesh size were adjusted, which were 39.56  0.029 and 81 cm2, respectively, they were found to be sufficient for the mean MPO area. It was found that the mesh size was sufficient for the mean MPO area. Conclusion: A mesh size of 10 × 15 cm is found to be the appropriate size to cover the MPO among Thais.